Occupational Exposures and Chronic Airflow Limitation - Helen Dimich-Ward; Susan M Kennedy; Moira Chan-Yeung (Canadian Respiratory Journal)
The recent literature was reviewed to evaluate whether chronic airflow limitation is associated with occupational exposures to dusts. Only those studies that controlled for the effects of smoking were included. There is compelling evidence that exposure to inorganic dusts, such as from coal and hardrock mining or asbestos, are associated with the development of chronic airflow limitation, independently of pneumoconiosis. Nonsmoking gold miners are particularly at high risk of airflow obstruction and emphysema. Findings from studies of organic dusts, such as exposures to wood, cotton, grain or other agricultural dusts, or to mixed dust exposures, were less consistent but tended to show positive dose-response associations. In the majority of studies, no statistical interaction was shown between dust exposures and smoking; however, the effects of the dust exposures were often more pronounced. An occupational history should be considered, in addition to a smoking history, as an integral part of an investigation of chronic airflow limitation in a patient.